KINERJA KEUANGAN DITINJAU DARI ANALISIS RASIO PROFITABILITAS (STUDI PADA PT ERAJAYA SWASEMBADA PERIODE 2020-2023) - Cahyani, Rizky Nur; Etnika, Sinta; Barokah, Siti (House of Management and Business (HOMBIS) Journal, 2025)
Financial Performance Judging From Profitability Ratio Analysis (Study At Pt Erajaya Swasembada Period 2020-2023). This study aims to be able to see the company's financial performance in terms of profitability ratio analysis at PT Erajaya Swasembada for the 2020-2023 period. The research method used is descriptive qualitative. The data source comes from the financial report data of PT Erajaya Swasembada (secondary data) in the 2020-2023 period. The results of the study found that the company's financial performance based on profitability ratios including using Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE) andGross Profit Margin (GPM) still have not reached industry standards. Although it can be seen that the sales of PT Erajaya Swasembada are quite large and even experienced a significant increase, it is not necessarily categorized as a company that has good performance. The profit generated by the company must also be able to cover the company's assets and equity so that it can be said that the financial performance is good, but at PT Erajaya Swasembada the profit has not been able to return the assets and capital because the industry- standard profitability ratio has not been achieved. This condition indicates that PT Erajaya Swasembada needs to evaluate and improve the efficiency and effectiveness of profit, asset, and equity management to increase its profitability of PT Erajaya Swasembada.